2001
DOI: 10.4319/lo.2001.46.6.1249
|View full text |Cite
|
Sign up to set email alerts
|

Iron availability, cellular iron quotas, and nitrogen fixation in Trichodesmium

Abstract: Iron availability is suggested to be a primary factor limiting nitrogen fixation in the oceans. This hypothesis is principally based on cost-benefit analyses of iron quotas in the dominant nitrogen-fixing cyanobacteria, Trichodesmium spp., in the contemporary oceans. Although previous studies with Trichodesmium have indicated that iron availability enhanced nitrogen fixation and photosynthesis, no clear relationship has been reported between cellular iron quotas and nitrogen fixation. We re-examined the propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
331
3
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(361 citation statements)
references
References 50 publications
26
331
3
1
Order By: Relevance
“…In addition, the N 2 -fixation rate, which reaches a maximum at midday (23), was considerably slower at 750 ppm than at 380 ppm pCO 2 (P = 0.035 and 0.009, t test) (Table 1), with a decrease of 35% and 50% at low and high Fe′, respectively. As expected from previous studies, increasing Fe availability decreased the ratio of POC to particulate organic N (PON) (P = 0.026, t test; Table 1) and increased the chlorophyll a (Chl a):C (P = 0.01, t test) (24). However, pCO 2 /pH had no significant effect on either of these parameters.…”
Section: And N 2 Fixation and Particulate Organic C:particulate Orgmentioning
confidence: 44%
“…In addition, the N 2 -fixation rate, which reaches a maximum at midday (23), was considerably slower at 750 ppm than at 380 ppm pCO 2 (P = 0.035 and 0.009, t test) (Table 1), with a decrease of 35% and 50% at low and high Fe′, respectively. As expected from previous studies, increasing Fe availability decreased the ratio of POC to particulate organic N (PON) (P = 0.026, t test; Table 1) and increased the chlorophyll a (Chl a):C (P = 0.01, t test) (24). However, pCO 2 /pH had no significant effect on either of these parameters.…”
Section: And N 2 Fixation and Particulate Organic C:particulate Orgmentioning
confidence: 44%
“…The low nutrient and low chlorophyll North Atlantic Ocean is thought to be one of the most iron-rich oceans owing to eolian inputs (Jickells et al, 2005) and has diverse communities of diazotrophs (Orcutt et al, 2001;Langlois et al, 2008). Actively N 2 -fixing Trichodesmium requires more Fe relative to non-diazotrophic phytoplankton (Berman-Frank et al, 2001), however in the Atlantic its growth was suggested to be either P (Sanudo-Wilhelmy et al, 2001;Hynes et al, 2009) or Fe (Lenes et al, 2001) limited. Co-limitation of bulk N 2 fixation by P and Fe was reported (Mills et al, 2004), suggesting both nutrients may become limiting for diazotrophs in this ocean basin, supported by recent in situ gene expression data (Webb et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As a key species in the marine ecosystem, Trichodesmium was used in several studies on the regulation of N 2 fixation (e.g., Berman-Frank et al 2001a, b, 2007Capone et al 2005;Kana 1993;Mulholland et al 2004). Unlike other diazotrophs, this species has evolved special features allowing N 2 fixation to occur during the photoperiod.…”
Section: Introductionmentioning
confidence: 99%
“…To protect the oxygen-sensitive enzyme nitrogenase, which catalyzes the reduction of N 2 to NH 3 , from photosynthetic O 2 evolution, this species has developed distinct diurnal rhythms in photosynthesis and N 2 fixation (Berman-Frank et al 2001b). By now, the genome of Trichodesmium IMS101 has been fully sequenced (US Department of Energy Joint Genome Institute http://www.jgi.doe.gov/) and several aspects of its ecophysiology have been studied, e.g., effects of phosphorus, iron limitation, temperature, salinity, and irradiance (Berman-Frank et al 2001a;Breitbarth et al 2008;Fu and Bell 2003). The potential influence of CO 2 -induced changes in seawater chemistry or combined effects of different environmental factors have, however, been ignored for a long time.…”
Section: Introductionmentioning
confidence: 99%